Bruise Susceptibility and Impact on Quality Parameters of Pears During Storage - Pathare, Pankaj B.; Al-Dairi, Mai (Frontiers in Sustainable Food Systems, 2021)
Bruise damage is one of the mechanical injury problems that could appear in fresh produce during the post-harvest supply chain. The study investigated three main effects (drop impact level, storage temperature, and storage duration), which can expand the level of bruising and cause some quality changes that contribute to the damage of pear. Pear fruit samples were purchased from the market and delivered to the post-harvest laboratory. Each pear was impacted by a ball with a known mass at three different drop heights (20, 40, and 60 cm), stored at 22°C with 45 ± 5% RH and 10°C with 85 ± 5% RH for 14 days storage period. Bruise area (BA), bruise volume (BV), and bruise susceptibility (BS) were calculated. Different quality analyses were done like color, firmness, and total soluble solids (TSS). Analysis of variance (ANOVA), regression analysis, and pearson correlation coefficient were performed. With increasing drop height and temperature for 14 days storage, BA, BV, BS, lightness (L*), yellowness (b*), color saturation (Chroma), and total color difference increased. However, firmness was highly reduced (92.82%) due to the increase in drop height (60 cm), storage temperature (22°C), and storage duration (14 days). Color purity (Hue), redness (a*), and TSS were not affected by drop height (impact level). A strong relationship with a strong linear regression (R2) was found between BS and CIE L*, a*, and b* color coordinates. A positive and strong correlation was also found between BS and CIEL*a*b* color parameters with a strong and negative correlation with firmness. Overall, this study can be considered as guideline for horticulture researchers and in fresh produce supply chain during post-harvest operations.